Influence on Vertical Shading Device Orientation and Thickness on the Natural Ventilation and Acoustical Performance of a Double Skin Facade. (2015) - Lee, Jeehwan; Chang, Jae D.
Abstract: A research showed that shading devices integrated within double skin facades (DSFs) could not only decrease direct solar heat gain but also screen unwanted sound transmission. Many researches also indicated that shading device configuration affected airflow patterns, the air velocity, and the air temperature in a DSF air cavity. At acoustical standpoints, other researches described that shading devices acted as sound barriers, however, the area of a DSF's vent opening could led to an increase in noise transmission. Therefore, the proper controls of shading devices inside a DSF air cavity can contribute to thermal and acoustical comfort with avoiding overheating and noise transmission. This study aimed at evaluating the correlation between natural ventilation potential and noise transmission loss based on the degree of orientation and thickness of vertical shading devices inside a DSF air cavity. The initial findings indicated that vertical shading devices should be controlled appropriately for balancing the requirements of thermal performance, natural ventilation efficiency and noise transmission loss.